The Role of Male and Female Nurse Shift Divisions in Prevention Allegations Abuse In the Emergency Room - Evani Christiani; Minarti, Karisma Sekar Ainun; Lytania Kusumaningtyas; Rheiny Desvia Putri (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
The Intensive Care Unit (SICU) is a vital part of the healthcare system, requiring intensive interaction between medical personnel and critically ill patients. This situation poses a potential risk of abuse of authority, including allegations of sexual harassment. One preventative measure that hospital management can take is through fair and strategic gender-based nurse shift allocation. This study aims to analyze the effect of gender-based shift allocation for male and female nurses in preventing allegations of harassment in the SICU, identify factors contributing to the risk of harassment, and assess the potential for legal violations that may arise from such actions. This study used a qualitative approach with normative juridical methods and was supported by empirical data from literature studies and media reports. The analysis results indicate that gender-balanced shift distribution can create a safer work environment and reduce the likelihood of harassment. Furthermore, factors such as minimal supervision, lack of professional ethics training, and weak victim protection also increase the potential for such incidents. From a legal perspective, harassment by healthcare workers violates the Criminal Code, the Health Law, and the nursing professional code of ethics. Therefore, proportional gender-based shift allocation can be a strategic step in preventing legal violations in the healthcare sector.